Candidaemia in cancer patients and in children in a neonatal intensive care unit - Trubenová, D; Virágová, S; Pilipcinec, E; Danko, J; Svický, E; Tkáciková, L (Folia microbiologica, 2001)
The species most frequently found in the group of neonates was C. parapsilosis, its incidence reaching 48%. Other yeasts isolated from blood were C. albicans (41%), C. tropicalis (7%), C. krusei and C. pseudotropicalis (2% each). Six yeast species (C. albicans 44%, C. parapsilosis 28%, C. tropicalis 11%, C. krusei 8%, C. guilliermondii 6%, C. lusitaniae 3%) were detected in cancer patients. The presence of an intravenous catheter as a possible risk in the development of candidaemia was identified in all neonates and in 69% of cancer patients. C. krusei candidaemia was associated with prophylactic fluconazole therapy.
Keywords: Child, Preschool; Slovakia; fungemie; Candida; Slovenská republika; Neoplasms; Adolescent; Child; dítě; Adult; Aged; dospělí; senioři; incidence; jednotky intenzivní péče o novorozence; kandidóza; mladiství; předškolní dítě; lidé; Candidiasis; Humans; Fungemia; Intensive Care Units, Neonatal; nádory; lidé středního věku; Incidence; Middle Aged